Phytochemical Screening on Some Leaves and Fruits Consumed by Javan Gibbons (Hylobates Moloch) from Cikaniki Area, Mount Halimun Salak National Park, West Java - Astri Zulfa; Muhamad Arif Wibisono; Muhammad Fathir Mulki; Jim Ron; Misbah Satria Giri; Rahayu Oktaviani (Universitas Nasional Jakarta, 2021)
Javan gibbon (Hylobates moloch) consumes different species of food, including fruits, leaves, flowers and insects. The food eaten by Hylobates moloch contains beneficial chemical compounds. One type of chemical compound found in Hylobates moloch food plants is secondary metabolite compounds that can affect also to feeding behavior. Secondary metabolites are chemical compounds in a plant that do not play a direct role in the needs of the plant's life but play a direct role in its environment. Several groups of secondary metabolites found in Hylobates moloch food plants include alkaloids, flavonoids, saponins, and tannins. The secondary metabolite compounds in these plants have potential as medicines. A sampling of Hylobates moloch food plant was taken from the Cikaniki area, Mount Halimun Salak National Park, West Java, based on the results of interviews with local communities and the research was continued with phytochemical tests. The results obtained 23 samples from 22 species of Hylobates moloch food which are included in 13 plant families, consisting of 18 types of leaves and 5 types of fruit. The results of qualitative phytochemical tests carried out on 23 samples of Hylobates moloch food plants obtained alkaloids, flavonoids, saponins, and tannins. The results of interviews with communities and literature studies show that Hylobates moloch food plants that are often used as medicine to cure certain diseases include: Dysoxylum parasiticum, Euodia latifolia, and Cinnamomum parthenoxylon